2010
DOI: 10.1002/psc.1290
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanotube‐coupled cell adhesion peptides are non‐immunogenic: a promising step toward new biomedical devices

Abstract: Carbon nanotubes functionalized with cell adhesion peptides can be considered as novel, promising candidates for the development of advanced drug delivery systems or for designing new generation of self-assembling nerve 'bridges'. An important step toward the integration of these types of conjugates in living bodies is the assessment of their impact on the immune system. In this direction, an integrin-derived peptide has been covalently conjugated to carbon nanotubes. Following intraperitoneal administration, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…Oxidized and 1,3-dipolar cycloaddition functionalized MWNTs(ox-MWNT-NH 3 + ) were prepared as reported in references 27,40 . The amount of amino groups was determined with the Kaiser test, corresponding to 170 µmol/g.…”
Section: Chemical Functionalization Of Multiwalled Carbon Nanotubesmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidized and 1,3-dipolar cycloaddition functionalized MWNTs(ox-MWNT-NH 3 + ) were prepared as reported in references 27,40 . The amount of amino groups was determined with the Kaiser test, corresponding to 170 µmol/g.…”
Section: Chemical Functionalization Of Multiwalled Carbon Nanotubesmentioning
confidence: 99%
“…[19][20][21][22] On the other hand, chemical functionalization of CNTs primarily developed to overcome their inherent hydrophobicity and lack of dispersibility in aqueous media [23][24][25] was found to significantly modulate the reported CNT toxicity or immunogenicity when compared to pristine (as produced) CNTs. [26][27][28][29] Demonstration of the potential of CNT-based constructs for transport of therapeutic or diagnostic agents to the brain parenchyma has progressed, however evaluation of the neurotoxicological profile of CNTs is still limited and certainly inconclusive. 30,31 In a study investigating the impact of CNTs on primary mixed neuro-glial cell cultures of the peripheral and central nervous system, 32 Belyanskaya et al have demonstrated higher cytotoxicity on glial cells than on neurons, with peripheral neural cells being more affected than their central counterparts.…”
mentioning
confidence: 99%
“…Recent studies have shown that, although the physicochemical characteristics of SWCNTs, including their highly hydrophobic surface, insolubility in aqueous solutions and contamination with metals used in the manufacturing process lead to their toxicity and poor biocompatibility, carefully optimizing these physicochemical parameters to minimize the toxicity of CNTs is highly advantageous and can be used in biomedical applications (Lanone et al, 2013). Based on literature reports that processing pristine SWCNTs in strong acids (3:1 mixture of H 2 SO 4 and HNO 3 ) in conjunction with sonication can remove residual metallic catalysts or amorphous carbon impurities and shorten the SWNTs (Villa et al, 2008;Gaillard et al, 2009), as well as the nature of PC and PVP K30 as non-toxic lipids and dispersants, respectively, we chose to use acid, PC, PVP K30 and ultrasonication to process the SWCNTs. Following the oxidative modification ( Figure 2B) and non-covalent functionalization ( Figure 3A, B) of the SWCNTs, their dispersibility significantly increased ( Figure 1A).…”
Section: Determination Of Functionalized Swcnts In Swcnt-curmentioning
confidence: 99%
“…Inflammatory mechanism of CNT cytoxicity was explored in detail by several investigators in pulmonary inflammation [44][45][46][47][48][49][50]). Monolayer cultures of epithelial, fibroblasts and smooth muscle cells were ideally used as experimental control of the system to test toxicity of CNTs without any cell-cell interactions.…”
Section: Inflammatory Mechanism Of Cnt Cytoxicitymentioning
confidence: 99%